Patient Management Strategies in Perioperative, Intraoperative, and Postoperative Period in Breast Reconstruction With DIEP-Flap: Clinical Recommendations - Chen, Kuo; Beeraka, Narasimha M.; Sinelnikov, Mikhail Y.; Zhang, Jin; Song, Dajiang; Gu, Yuanting; Li, Jingruo; Reshetov, I. V.; Startseva, O. I.; Liu, Junqi; Fan, Ruitai; Lu, Pengwei (Frontiers in Surgery, 2022)
Background and Objective Deep Inferior Epigastric Perforator (DIEP) flap is a tissue isolated from the skin and subcutaneous tissue of the lower abdomen or rectus muscle to foster breast reconstruction. There is limited information about DIEP-flap induced complications associated with breast reconstruction surgery. Evidence We conducted a systematic review of the published literature in the field of breast cancer reconstruction surgery. Information was gathered through internet resources such as PubMed, Medline, eMedicine, NLM, and ReleMed etc. The following key phrases were used for effective literature collection: “DIEP flap”, “Breast reconstruction”, “Patient management”, “Postoperative DIEP”, “Intraoperative anticoagulant therapy”, “Clinical recommendations”. A total of 106 research papers were retrieved pertaining to this systematic review. Conclusion A successful breast reconstruction with DIEP-flap without complications is the priority achievement for this surgical procedure. This study provides various evidence-based recommendations on patient management in the perioperative, intraoperative, and postoperative periods. The clinical recommendations provided in this review can benefit surgeons to execute breast reconstruction surgery with minimal postoperative complications. These recommendations are beneficial to improve clinical outcomes when performing surgery by minimizing complications in perioperative, intraoperative, and postoperative period.